"Be Fertile and Increase, Fill the Earth and Master It" The Ancient and Medieval Career of a Biblical Text - Cohen, Jeremy (Cornell University Press, 2019)
This innovative, interdisciplinary book reconstructs the career of Genesis 1:28 ("Be fertile and increase, fill the earth and master it...") in Judaism and Christianity, from antiquity through the Reformation. Jeremy Cohen tracks the text through all the Jewish and Christian sources in which it figures significantly-in law, exegesis, homily, theology, mysticism, philosophy, and even vernacular poetry. In his view, the verse situates man and woman on a cosmic frontier, midway between the angelic and the bestial, charging them with singular responsibilities that bear directly on Jewish and Christian ideas of God's "chosen people."